Implementation of Web-based Online Examination for High School Students - Khumaini, Hayatullah; Pratiwi, Fitri; Daulay, Jamil; Putra, Al Malikul Ikhwanda; Rubiati, Nur (Brilliance: Research of Artificial Intelligence, 2024)
Examination is a form of evaluation of the learning process to measure the achievement of student intelligence in schools. The implementation of conventional exams that are often carried out by schools has the potential for fraud both from students who cheat during the exam or leak exam questions before the exam takes place and also the operational costs that must be incurred by schools to duplicate questions and coupled with teachers needing additional time to check student exam results. In addition to being carried out in writing or orally, exams can also be carried out using computer aids. With the help of this study, teachers will be able to create questions without worrying that they will be leaked to students before the test and share them with other educators teaching the same subject. Students should be able to receive exam results right away after the test is over, and teachers won't have to worry about checking the results because they will be sent to them automatically. For schools, the costs incurred for paper can be reduced with this online exam system. The results of this research are in the form of a web-based application with the concept of client server using the help of a framework that already supports the model, view and controller system. This application has users, where there are several users with differentiators in the form of access rights.